(untitled) (Islamic Sciences Journal, 2026)
The research addressed the topic of "The Quranic Guidance Assurance for Family Building and Human Problems Treatment" as one of the fundamental pillars for building a society. It emphasized that the family, being the smallest unit of society, is crucial for societal success or failure. The research focused on the importance of preparing and nurturing families correctly, highlighting the pivotal role of the family in reforming and solving societal problems. It stressed that the Quranic guidance provides the means to address these issues and ensure the well-being of the community. The study consisted of an introduction and two main sections. The introduction outlined the significance of the topic and the research plan, while the first section defined the concept of the family and emphasized its importance according to the Quran. The second section discussed the principles of family formation and the essential solutions to its problems through Quranic guidance. The research concluded with key findings and recommendations.